Strategi Komunikasi Interpersonal Pegawai Tata Usaha STFI Dalam Pelayanan Mahasiswa Era Digitalisasi - Panca Putra, Nabil Hanan; Tawaqal, Rizki Surya (Komunika : Jurnal Ilmiah Komunikasi, 2025)
The purpose of this study is to examine the interaction between administrative and household staff and students at the Indonesian College of Pharmacy, and to identify communication problems faced by students when using academic services in the digital age. Data was collected thru in-depth interviews with eight active students from various majors who had previously received administrative services either in person or thru digital media such as email and WhatsApp messages. This research uses a descriptive qualitative approach. Data was analyzed using an interactive model developed by Miles Huberman and Saldanha. Translation: Summarizing, presenting data, and simplifying information – all of these are part of this model. Direct communication is considered more effective, friendly, and provides greater confidence in service compared to communication thru digital media. Because the office staff are friendly, approachable, and explain administrative processes well, students prefer to get direct help from them. However, due to communication system issues and high staff workload in digital communication, problems such as slow responses, inconsistent responses, and missed messages still persist. Additionally, management issues such as untimely information delivery also affect service to students. According to this research, direct communication between employes is already good, but to improve service to students, more structured and sustainable communication management strategies and digital service systems are needed.